La estimulación temprana y su incidencia en el desarrollo psicomotriz de los niños y niñas de educación inicial 2 del centro de educación infantil Su Majestad el Niño de la ciudad de Catacocha, cantón Paltas, provincia de Loja. Período lectivo 2013- 2014. Lineamientos alternativos - Lalangui Martinez, Gina Tatiana (2014)
This research entitled "EARLY STIMULATION AND ITS IMPACT ON DEVELOPMENT PSYCHOMOTOR CHILDREN OF PRESCHOOL EDUCATION 2 PRESECHOOL EDUCATION CHILDREN PSYCHOMOTOR " SU MAJESTAD EL NIÑO" CHIRDRENS EDUCATIONAL CENTER PALTAS CANTON, LOJA PROVINCE . LECTIVO PERIOD 2013 -. 2014 " ALTERNATIVE GUIDELINES, IT IS STRUCTURED BASED ON THE CURRENT REGULATIONS ACADEMIC SYSTEM AT THE NATIONAL UNIVERSITY OF LOJA. The general objective that guided the research process was: To establish the incidence of early stimulation in the Psychomotor development of children 2 Early Childhood Education Early Childhood Center " HM El Niño" Catacocha City Region Avocado , province of Loja. Teaching period 2013-2014 The methods used were : Scientist, Inductive, Deductive , Descriptive and Statistical Model . The techniques applied were: Survey applied to teachers of The general objective that guided the research process was: To establish the incidence of PRESCHOOL EDUCATION CHILDREN “Su Majestad el Niño” chilshood educational centers.Teaching period 2013-2014 , to identify activities Early Stimulation engaged in their daily work; and, Test of Motor Proficiency Oseretzky applied to children. In the implementation of the survey it was found that teachers : 100% of teachers engaged in Early Stimulation with children such as playgroups, literature, art and visual expression techniques graph and 67% puppets. According to results of Motor Ability Test Oseretzky , the following result was obtained : 81% of children have a Psychomotor development satisfactory and 19% unsatisfactory ..